Performance of Low Power Wind-Driven Wound Rotor Induction Generators using Matlab (International Journal of Current Engineering and Technology, 2014)
Various techniques have been employed to optimize the performance of wound rotor induction generator (WRIG) based wind power generation systems. Input voltage control was used for the improvement of power factor in grid-connected induction generators. However, here, efficiency reduces drastically because of high output current. Moreover, the control range is limited. The conventional rotor resistance control had also been used for wind-driven WRIG. But, the input power factor becomes very poor. In this paper, a new control method is analyzed where both input voltage and slip power control are used together to achieve better performance. For each operating point an optimum input voltage is set and slip is controlled by rotor resistance such that the maximum efficiency is obtained. Moreover, both power factor and efficiency are improved for a wide range of speed variations. Also the reactive power demand is reduced throughout the range of effective speed which is compensated by optimum fixed capacitors. This scheme is useful for low power wind energy conversion system (WECS) where wind speed varies over wide range. Simulation model for the proposed schemes are developed using MATLAB and the performance of the induction generator under various wind conditions are studied with this model. Also the performance characteristics of the schemes are experimentally verified. The new control schemes are cheap.
Keywords: Combined input voltage and slip power control, Wound Rotor Induction generator (WRIG), MATLAB, Slip power control, Renewable energy sources (RES), Wind energy conversion system (WECS).